Dendritic cell derived exosomes loaded with immunoregulatory cargo reprogram local immune responses and inhibit degenerative bone disease in vivo. Issue 1 (7th August 2020) - Elashiry, Mahmoud; Elashiry, Mohamed M.; Elsayed, Ranya; Rajendran, Mythily; Auersvald, Carol; Zeitoun, Rana; Rashid, Mohammad H.; Ara, Roxan; Meghil, Mohamed M.; Liu, Yutao; Arbab, Ali S.; Arce, Roger M.; et al.
ABSTRACT: Chronic bone degenerative diseases represent a major threat to the health and well‐being of the population, particularly those with advanced age. This study isolated exosomes (EXO), natural nano‐particles, from dendritic cells, the "directors" of the immune response, to examine the immunobiology of DC EXO in mice, and their ability to reprogram immune cells responsible for experimental alveolar bone loss in vivo . Distinct DC EXO subtypes including immune‐regulatory (regDC EXO), loaded with TGFB1 and IL10 after purification, along with immune stimulatory (stimDC EXO) and immune "null" immature (iDCs EXO) unmodified after purification, were delivered via I.V. route or locally into the soft tissues overlying the alveolar bone. Locally administrated regDC EXO showed high affinity for inflamed sites, and were taken up by both DCs and T cells in situ . RegDC EXO‐encapsulated immunoregulatory cargo (TGFB1 and IL10) was protected from proteolytic degradation. Moreover, maturation of recipient DCs and induction of Th17 effectors was suppressed by regDC EXO, while T‐regulatory cell recruitment was promoted, resulting in inhibition of bone resorptive cytokines and reduction in osteoclastic bone loss. This work is the first demonstration of DC exosome‐based therapy for a degenerative alveolar bone disease and provides the basis for a novel treatment strategy.